Dietary Lasia spinosa Thw. Improves Growth Performance in Broilers - Zhang, Lang; Hong, Yongxing; Liao, Yuying; Tian, Kui; Sun, Haodong; Liu, Xingting; Tang, Yanfei; Hassanin, Abdallah A.; Abdelnour, Sameh A.; Suthikrai, Wanwipa; Srisakwattana, Kittiya; Tharasanit, Theerawat; et al. (Frontiers in Nutrition, 2022)
This study aimed to evaluate the effects of dietary Lasia spinosa Thw. (LST) powder supplementation on growth performance, blood metabolites, antioxidant status, intestinal morphology and cecal microbiome in broiler chickens. A total of 400 one-day-old male Guangxi Partridge broilers (initial body weight: 42.52± 0.06 g) were randomly allotted to 4 dietary treatments: LST0 group (a basal diet), LST1 group (a basal diet with 1% LST powder), LST2 group (a basal diet with 2% LST powder), LST4 group (a basal diet with 4% LST powder), ten replicates for each treatment and 10 broilers in each treatment group. Results indicated that the average daily feed intake of broilers during 22-42 d and the average daily gain of chickens during 1-42 d significantly increased by dietary supplementation of LST powder (P<0.01), while the feed conversion ratio during the overall periods was decreased (P<0.01). The levels of SOD, CAT and GSH-Px in serum, liver and breast muscle were significantly increased in LST supplemented groups (P<0.05), while ROS and MDA in serum, liver and breast muscle were decreased (P<0.05). Furthermore, the levels of TG and LDL-C were significantly decreased by the addition of dietary LST powder (P<0.01), while levels of HDL-C, Ca, Fe, Mg and P were linearly increased (P<0.01). Regarding the gut morphometric, crypt depth was significantly decreased by LST supplementation (P<0.05), while villus height and the ratio of villus height to crypt depth were notably increased (P<0.05). Sequencing of 16S rRNA from the cecal contents of broilers revealed that the composition of the chicken gut microbiota was altered by LST supplementation. The diversity of microbiota in broilers was increased (P<0.05) in the LST1 groups but was decreased (P<0.05) in the LST2 and LST4 groups compared with LST0 groups. The differential genera enriched in LST1 groups, such as Bacillus, Odoribacter, Sutterella, Anaerofilum, Peptococcus, were closely related to the increased growth performance, antioxidant status, intestinal morphology, Ca, Mg and reduced blood lipid in the treated broilers.